Pengaruh Pemeriksaan Pajak dan Sanksi Pajak Terhadap Penerimaan Pajak Penghasilan Orang Pribadi Pada KPP Pratama Bojonagara - Meilinda, Neng; Mulyana, Asep; Rizki, Nonon Dherian; Dwitasari, Anita Theresia; Al'libani, Ridha Rahim (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the influence of tax audits and tax sanctions on the income tax (PPh) revenue from individual taxpayers at the Pratama Tax Office (KPP) Bandung Bojonagara during the 2016–2024 period. The research method used is a quantitative research method with a multiple linear regression analysis model. The data used is secondary data. The results of the study show that Tax Audit partially has no effect on Personal Income Tax Revenue, while Tax Sanctions partially have a significant effect on Personal Income Tax Receipt. Tax Audit and Tax Sanctions simultaneously have a significant effect on Personal Income Tax Revenue.